Effectiveness of the Successful Parenting Training Program on Parental Stress, Children’s Anxiety, and Family Functioning - Taghikhani, Ghazal; Goudarzi, Mahmoud; Ahmadian, Hamzeh (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Successful parenting is a novel and universal program about parenting that fosters positive relationships between parents and their children. Therefore, the aim of the present study was to determine the effect of successful parenting training on family functioning, children’s anxiety, and parental stress. Methods and Materials: The research method was quasi-experimental with a pre-test-post-test design and a control group. The statistical population included all parents (with diversity in variance and not merely successful parents) and all elementary school students studying in elementary schools in the city of Isfahan in the 2021-2022 academic year. From this population, 32 individuals (16 couples) were sampled and assigned to two groups of 16 individuals (8 couples) each for the experimental and control groups. Participants completed the Spence Children’s Anxiety Scale (2003), the Abidin Parental Stress Index (1995), and the Family Assessment Device by Epstein, Baldwin, and Bishop (1950) in the pre-test and post-test phases. The experimental group underwent a 15-session intervention protocol based on the successful parenting model derived from the final model of this research. Findings: Results of the univariate covariance analysis showed that the experimental group, receiving the intervention based on successful parenting training, exhibited significantly higher family functioning and lower children’s anxiety and parental stress compared to the control group (p < 0.01). Conclusion: Given the results of this study, it is recommended to employ successful parenting training to enhance family functioning and reduce children’s anxiety and stress.